A note on the harbour seal (Phoca vitulina) in the Faroe Islands - Mikkelsen, Bjarni (NAMMCO Scientific Publications, 2010)
The harbour seal was exterminated as a breeding species in the Faroe Islands in the mid-19th Century. Historical sources document that the harbour seal used to be a common inhabitant of the sheltered fjords where breeding occurred. It was reported to be more common than the grey seal, the other pinniped specie resident around the Faroes. But the number of harbour seals seemingly decreased as human settlements and other anthropogenic activities increased. Seal hunting was apparently already introduced by the Norse that arrived on the islands in the 7th century, a hunt that finally lead to the extermination of the harbour seal. For the last 40 years the harbour seal has only been positively identified twice in the Faroe Islands, in 2001 and 2005.